Inflation in supergravity and the volume modulus - Bernardo, H. de O [UNESP] (2015)
In this master thesis we attempt to implement inflation in supergravity with the volume modulus of large extra dimensions acting as the inflaton. The Langragian of chiral matter coupled with supergravity is derived from first principles and we review the standard cosmology and the consequences of an inflationary universe. Then we proceed to the analysis of inflation in supergravity and explain what are extra dimensions. Lastly, we construct a model of new inflation and look for its compatibility with the observacional results obtained from the Planck datellite